Environmental effects of nitrogen oxides and hydrocarbons from road traffic in Sweden. Miljoeeffekter av kvaeveoxider och kolvaeten fraan vaegtrafik i Sverige - "Sjoedin, Aa"; "Omstedt, G"; "Calander, K"; "Ahlfors, A"; "Pleijel, H [Swedish Environmental Research Institute, Goeteborg (SE)]" (1990)
This study attempted to evaluate the effects on vegetation as a result of the emissions of nitrogen oxides and hydrocarbons from the Swedish road traffic on local, regional and national scales. The first part of the report consists of a summary of present knowledge concerning the emissions of nitrogen oxides and hydrocarbons from road traffic, their chemical conversion and dynamics in the atmosphere, and the most important effects on nature. In the second part of the report, the role road traffic plays for the emission of nitrogen oxides and hydrocarbons, and for nitrogen deposition and ozone formation in Sweden is analyzed. Different calculation models have been used in estimates of the contribution of road traffic to concentrations and deposition. The results are used in preparing the evaluation of the environmental effect that makes the third and final part of the report. Today, road traffic in Sweden accounts for about half of the total emissions of nitrogen oxides and hydrocarbons. The emissions are very unevenly distributed throughout the country. The introduction of catalytic cleaning of exhaust gases on petrol-powered cars and more severe demands placed on heavy traffic are estimated to lead to a decrease of 40-60 per cent in the emissions of nitrogen oxides from road traffic in Sweden between 1985 and 2010. The reduction is anticipated to be even greater with regard to emissions of hydrocarbons. (au).
Keywords: "54 ENVIRONMENTAL SCIENCES"; "HYDROCARBONS"; "ENVIRONMENTAL EFFECTS"; "NITROGEN OXIDES"; "AIR POLLUTION"; "AUTOMOBILES"; "OZONE"; "ROAD TRANSPORT"; "SWEDEN"; "TRUCKS"; "CHALCOGENIDES"; "DEVELOPED COUNTRIES"; "EUROPE"; "LAND TRANSPORT"; "NITROGEN COMPOUNDS"; "ORGANIC COMPOUNDS"; "OXIDES"; "OXYGEN COMPOUNDS"; "POLLUTION"; "SCANDINAVIA"; "TRANSPORT"; "VEHICLES"; "540120* - Environment, Atmospheric- Chemicals Monitoring & Transport- (1990-)"